Digital Marketing Strategy for Service Providers at LKP Aulia Electronic Training Center - Nurafrina Siregar; Toto Budiharto (Yayasan Multidimensi Kreatif, 2024)
This study discusses the digital marketing strategy implemented by CV. Aulia Berkah Utama, a service company in North Sumatra, to improve service effectiveness and expand market reach. In the era of digital transformation, the use of technology-based marketing strategies is very important to face increasingly fierce competition. The methods used in this study include the analysis of various digital platforms such as social media, search engines, and the company's official website . The results of the study indicate that the implementation of a structured digital marketing strategy , such as social media optimization, the use of paid advertising, and SEO optimization, can increase service visibility and improve customer interactions. The conclusion of this study emphasizes the importance of consistency and innovation in digital strategies to maintain competitiveness and strengthen consumer trust.